Prognostic significance of the methylation of Wnt pathway antagonists-CXXC4, DACT2, and the inhibitors of sonic hedgehog signaling-ZIC1, ZIC4, and HHIP in head and neck squamous cell carcinomas - Paluszczak Jarosław; Wiśniewska Dorota; Kostrzewska-Poczekaj Magdalena; Kiwerska Katarzyna; Grénman Reidar; Mielcarek-Kuchta Daniela; Jarmuż-Szymczak Małgorzata (SPRINGER HEIDELBERG, 2022)
Aberrations in Wnt and Shh signaling pathways are related to the pathogenesis of head and neck carcinomas, and their activation frequently results from epigenetic alterations. This study aimed to assess the frequency of methylation of negative regulators of Wnt signaling: CXXC4, DACT2, HDPR1, and FBXW11 and Shh signaling: HHIP, PTCH1, SUFU, ZIC1, and ZIC4 and correlate it with clinicopathological features in this group of patients.Methylation-specific PCR was used to detect gene promoter methylation, and real-time PCR was used to assess gene expression level.The analysis of the occurrence of gene promoter methylation in head and neck carcinoma cell lines indicated that CXXC4, DACT2, HHIP, ZIC1, and ZIC4 are methylated in these tumors. These genes were further analyzed in tumor sections from oral and laryngeal cancer patients. Gene methylation rate was higher in laryngeal tumors. The methylation index in tumor samples correlated with the overall survival in a subgroup of oral cancer patients who died of the disease. Moreover, ZIC4 methylation correlated with lymph node involvement in oral cancer patients.Our findings corroborate that the activation of Wnt signaling in head and neck squamous cell carcinoma (HNSCC) is related to epigenetic silencing of its negative regulators. Moreover, the results indicate that the same mechanism of activation may operate in the case of Shh signaling.The methylation of ZIC4 may be considered a new prognostic marker in oral cavity and oropharyngeal tumors. Further investigations should determine the diagnostic significance of methylation of ZIC4, HHIP, and DACT2 in head and neck carcinomas.